2019
DOI: 10.1111/codi.14877
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pelvic pain and rectal prolapse invite consideration of enterocele

Abstract: Aim Data on the pathogenesis and symptoms of enterocele are limited. The objectives of this study were to determine the clinical phenotype of patients with enterocele, to highlight the main functional and/or anatomical associations and to improve the accuracy of the preoperative assessment of pelvic floor disorders. Method A total of 588 patients who were referred to a tertiary unit for an anorectal complaint completed a self‐administered questionnaire and underwent physical examination, anorectal manometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…IBS and hernia have similar symptoms, such as abdominal pain, constipation, and diarrhea, but few studies have focused on the association between these two diseases. One study focused on 558 patients with small bowel hernia and observed that IBS was more common in these patients than in those without enterocele [32]. Although the pathogenesis of IBS and diverticular disease remains incompletely understood, substantial overlap or coexistence of these two diseases has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…IBS and hernia have similar symptoms, such as abdominal pain, constipation, and diarrhea, but few studies have focused on the association between these two diseases. One study focused on 558 patients with small bowel hernia and observed that IBS was more common in these patients than in those without enterocele [32]. Although the pathogenesis of IBS and diverticular disease remains incompletely understood, substantial overlap or coexistence of these two diseases has been observed.…”
Section: Discussionmentioning
confidence: 99%